Systematic Review of Changes and Recovery in Physical Function and Fitness After Severe Acute Respiratory Syndrome–Related Coronavirus Infection: Implications for COVID-19 Rehabilitation. Issue 10 (31st July 2020) - Rooney, Scott; Webster, Amy; Paul, Lorna
Abstract: Objective: This review sought to (1) compare physical function and fitness outcomes in people infected with Severe Acute Respiratory Syndrome-related Coronavirus (SARS-CoV) with healthy controls, (2) quantify the recovery of physical function and fitness following SARS-CoV infection, and (3) determine the effects of exercise following SARS-CoV infection. Methods: Four databases (CINAHL, MEDLINE, ProQuest, and Web of Science Core Collections) were searched in April 2020 using keywords relating to SARS-CoV, physical function, fitness, and exercise. Observational studies or randomized controlled trials were included if they involved people following SARS-CoV infection and either assessed the change or recovery in physical function/fitness or evaluated the effects exercise postinfection. Results: A total 10 articles were included in this review. Evidence from 9 articles demonstrated that SARS-CoV patients had reduced levels of physical function and fitness postinfection compared with healthy controls. Furthermore, patients demonstrated incomplete recovery of physical function, with some experiencing residual impairments 1 to 2 years postinfection. Evidence from 1 randomized controlled trial found that a combined aerobic and resistance training intervention significantly improved physical function and fitness postinfection compared with a control group. Conclusions: Physical function and fitness are impaired following SARS-CoV infection, and impairments may persist up to 1 to 2 years postinfection. Researchers and clinicians can use these findings to understand the potential impairments and rehabilitation needs of people recovering from the current coronavirus 2019 (COVID-19) outbreak. While 1 study demonstrated that exercise can improve physical function and fitness postinfection, further research is required to determine the effectiveness of exercise in people recovering from similar infections (eg, COVID-19). Impact: Considering the similarities in pathology and clinical presentation of SARS-CoV and COVID-19, it is likely that COVID-19 patients will present with similar impairments to physical function. Accordingly, research is required to measure the extent of functional impairments in COVID-19 cohorts. In addition, research should evaluate whether rehabilitation interventions such as exercise can promote postinfection recovery.